2020
DOI: 10.21203/rs.3.rs-47448/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Health Anxiety and Prenatal Distress with Choosing the Type of Childbirth in Pregnant Women during Covid-19 Outbreaks in Iran

Abstract: Background This study investigates the relationship between health anxiety and prenatal distress with choosing the type of childbirth in pregnant women during Covid-19 outbreaks in Iran.Methods This is a descriptive-analytical study on 200 nulliparous pregnant women who referred to health centers of Iran to perform routine pregnancy care. Convenient sampling was used, and each nulli pari pregnant woman who tended to enter the study was enrolled. The questionnaires used in this work were demographic and midwife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Contrary to the abovementioned studies, the study by Dagklis et al discovered no differences among the three trimesters of pregnancy regarding the incidence of anxiety (28). In Beheshtinasab et al study, there was no significant statistical association between gestational age (0.370) and health anxiety or prenatal distress scores (14). In the study by Berthelot et al, multivariate regressions were performed but no significant associations were observed between gestational age and the mood and anxiety symptoms (P=0.72) (39).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Contrary to the abovementioned studies, the study by Dagklis et al discovered no differences among the three trimesters of pregnancy regarding the incidence of anxiety (28). In Beheshtinasab et al study, there was no significant statistical association between gestational age (0.370) and health anxiety or prenatal distress scores (14). In the study by Berthelot et al, multivariate regressions were performed but no significant associations were observed between gestational age and the mood and anxiety symptoms (P=0.72) (39).…”
Section: Discussionmentioning
confidence: 81%
“…It should be noted that the cesarean section increases postpartum anxiety, stress, and depression, which can produce outcomes such as decline in fertility, increase in pregnancy intervals, and increase in labor risk in further pregnancies. Beheshtinasab et al suggested several reasons for the selection of cesarean section during of COVID-19 epidemic including: higher distress in the prenatal period as well as higher concern about the fetus rather than themselves, and fear of injury to baby during attempted vaginal delivery (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedasarkan hasil penelitian cara persalinan terbanyak yang dipilih oleh responden adalah persalinan secara SC yaitu sebanyak 167 responden (54.0%) dan sisanya sebanyak 142 responden (46.0%) memilih persalinan secara normal. Hal ini sesuai dengan penelitian Nasab (2020) bahwa lebih banyak ibu hamil yang memilih untuk melahirkan melalui operasi sesar di masa pandemi Covid-19 (Nasab et al, 2020). Pemilihan cara persalinan selama pandemi Covid-19 dapat dipengaruhi oleh peningkatan kecemasan yang dialami oleh Menurut peneliti salah satu alasan banyaknya ibu hamil yang lebih memilih persalinan secara SC selama pandemi Covid-19 adalah karena waktu dan durasi persalinan yang dapat ditentukan lebih pasti dibandingkan dengan persalinan normal sehingga ibu dan keluarga dapat merasa lebih tenang.…”
Section: Hasil Penelitian Dan Pembahasanunclassified
“…Ibu hamil akan lebih dipengaruhi oleh rasa cemas yang dirasakan dalam pengambilan keputusan cara persalinan yang akan dijalaninya. Hal ini didukung teori yang menyatakan bahwa sebagian besar ibu hamil mungkin akan memutuskan memilih persalinan secara SC karena berasumsi bahwa persalinan SC dapat mengurangi kemungkinan kontak virus Covid-19 antara ibu hamil dan bayi (Nasab et al, 2020). Bukti empiris juga menyebutkan bahwa stress pada ibu hamil yang cukup tinggi dapat mempengaruhi tingginya kejadian persalinan secara SC (Nwafor et al, 2021).…”
Section: Hasil Penelitian Dan Pembahasanunclassified